CHEMICAL TRANSFORMATIONS OF PYRIDOXAL CONDENSATION PRODUCTS WITH L-ɑ- HISTIDINE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The kinetics and mechanism of interaction of pyridoxal with L-α-histidine have been studied.L-α-histidine with pyridoxal proceeds through three kinetically different stages: the first fast stage is the addition of an amino acid to pyridoxal with the formation of an amino alcohol and its subsequent restructuring, the second, slower stage is the dehydration of amino alcohol with the formation of a Schiff base, and the third very slow stage is the cleavage of hydrogen CO2 from the L–α–amino acid fragment, restructuring Schiff bases into a quinoid structure, the subsequent hydrolysis of which leads to the formation of pyridoxal histamine. A scheme of chemical transformations of pyridoxal condensation products with L-α-histidine is proposed.
Keywords: Vitamins В6; Amino acids; Structure of amino acids and bases Schiff